Elaboración de un preparado magistral a base de ajo (Allium sativum) y caléndula (Calendula officinalis) y evaluación de su actividad antimicrobiana y antimicótica. - Bermúdez Hoyos, Maribel
In the present work, was developed a magistral formulation base on garlic and marigold for the treatment of dermatophytosis. The plants used were selected because of its traditional use as an antimicrobial and wound healing, respectively, easy to obtain in the market and vast scientific support of its active components. The secondary metabolites of the plant material was extracted using ethanol at different concentrations. The magistral formulation was developed, adding 10%, 20%, 30% and 40% of garlic extract, and 20% of marigold. Then, the bactericidal power, of each formulation, against Pseudomonas aeruginosa strain ATCC 9027 and Staphylococcus aureus strain ATCC 6538 was determined, with contact time of 5 minutes. The fungicide power against the dermatophyte fungus Trichophyton rubrum strain ATCC 28188 was determined, with contact time of 15 minutes. The cream with addition of 40% garlic extract, showed the best results with reduction of 99% for P. aeruginosa, 98.8% for S. aureus, and 99.9% for T. rubrum. The antimicrobial effect of the above formulation, could serve as a potential candidate for the development of new antifungal treatments. Additionally, with bactericidal properties, avoiding a possible infection, in a dermatophytosis, with transient flora.